2007
DOI: 10.1038/sj.gt.3303058
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo analysis of expression cassettes designed for vascular gene transfer

Abstract: Increasing the level and duration of transgene expression and restricting expression to vascular cells are important goals for clinically useful gene therapy vectors. We evaluated several promoters, enhancers and introns in endothelial, smooth muscle and liver cells in tissue culture and in vivo, comparing local delivery to the carotid artery with intravenous delivery to the liver. A 1800-bp fragment of the oxidized LDL receptor (LOX-1) promoter showed highest in vivo activity in the carotid artery, achieving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In conclusion, when compared to previous work that addresses either transcriptional control in HDAd or optimization of transgene expression in EC in vivo, 43,50 our results reveal new factors that influence the level and time course of transgene expression after in vivo transduction of EC with HDAd. These factors include susceptibility of the vector promoter to acute upregulation as well as feedback effects of transgene products (such as IL-10) on transgene expression.…”
Section: Discussionmentioning
confidence: 47%
“…In conclusion, when compared to previous work that addresses either transcriptional control in HDAd or optimization of transgene expression in EC in vivo, 43,50 our results reveal new factors that influence the level and time course of transgene expression after in vivo transduction of EC with HDAd. These factors include susceptibility of the vector promoter to acute upregulation as well as feedback effects of transgene products (such as IL-10) on transgene expression.…”
Section: Discussionmentioning
confidence: 47%
“…The need for an EC-specific cassette that achieves expression levels in large vessel EC at least as high as those obtained with the CMV promoter is well stated in a recent article by White et al 16. We pursued this goal using rabbit IL-10 cDNA and genomic clones, murine ET-1 promoter and enhancer sequences, and a post-transcriptional regulatory element (PRE).…”
Section: Discussionmentioning
confidence: 99%
“…In several cases relative EC-specificity was achieved compared to viral or broadly active eukaryotic promoters such as phosphoglycerate kinase. However, EC-specificity was acquired at the cost of reliably lower transgene expression 12,14,16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge was in generating an EC-specific promoter with comparable efficiency as the CMV promoter. White et al [120] examined several novel Ad expression cassettes for EC-specific gene transfer with CMV, Tshort, ICAM-2, ICAM-1, FLT-1 promoters, respectively and found that LOX-1 promoter elements significantly increased reporter gene expression in carotid arteries compared to other promoters. The efficacy of these novel expression cassettes in large animal models have yet to be established.…”
Section: Tissue-specific Targetingmentioning
confidence: 99%